1983
DOI: 10.1128/jcm.17.4.655-665.1983
|View full text |Cite
|
Sign up to set email alerts
|

Principles, problems, and strategies in the use of antigenic mixtures for the enzyme-linked immunosorbent assay

Abstract: Competition between proteins and other macromolecules for adsorption sites on plastic was studied with the enzyme-linked immunosorbent assay (ELISA) to determine effects of the use of antigenic mixtures or extracts of organisms on assays of antibodies and antigens by ELISA. A comparison of a number of different polystyrene microplates with bovine albumin and human immunoglobulin G (IgG) as antigens showed two major classes of plates: those which adsorbed albumin poorly and those which adsorbed albumin well. Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(24 citation statements)
references
References 16 publications
2
21
1
Order By: Relevance
“…High CF sera showed significantly high ELISA values not only for M. pneumoniae (P<0.001), but also for M. hyorhinis (P<0.001) and M. pulmonis (P=0.001). It is suspected that the main factor causing background readings is the nonspecific adsorption of serum and the conjugate on ELISA antigens or on the surface of plate wells (7,13,16). However, our results showed that the background readings found in ELISA for measuring antibodies to M. pneumoniae were not due to nonspecific adsorption of human IgG on the plate wells and on medium components which might have contaminated mycoplasmal ELISA antigens.…”
Section: Elisa Activity Of Human Sera For Some Mycoplasmascontrasting
confidence: 53%
“…High CF sera showed significantly high ELISA values not only for M. pneumoniae (P<0.001), but also for M. hyorhinis (P<0.001) and M. pulmonis (P=0.001). It is suspected that the main factor causing background readings is the nonspecific adsorption of serum and the conjugate on ELISA antigens or on the surface of plate wells (7,13,16). However, our results showed that the background readings found in ELISA for measuring antibodies to M. pneumoniae were not due to nonspecific adsorption of human IgG on the plate wells and on medium components which might have contaminated mycoplasmal ELISA antigens.…”
Section: Elisa Activity Of Human Sera For Some Mycoplasmascontrasting
confidence: 53%
“…An antigen in excess will block the binding of another in much smaller amounts leading to failure of detection of the minor antigen(s). This aspect of ELISA technology where antigen mixtures are assayed with single serum samples has been illustrated by Kenny & Dunsmoor (1983). Some antigens may not even bind at all but the use of single antigen assays would obviate this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Coating was performed in 0.1 M carbonate buffer pH 9.6 at a final concentration of 0.5 mg/ml of antibodies. The microtitre plates were thoroughly washed with PBS containing 3% Tween 20 (10). Samples diluted 1:20 in PBS containing 3% Tween 20 were tested in duplo, avoiding the outermost wells.…”
Section: Methodsmentioning
confidence: 99%